First-Line Therapy for Immune Thrombocytopenia - Mithoowani, Siraj; Arnold, Donald M. (Hämostaseologie, 2019)
Immune thrombocytopenia (ITP) is an autoimmune disease affecting blood platelets that causes thrombocytopenia and an increased risk of bleeding. First-line therapy is indicated for patients with bleeding complications or who are at increased risk of bleeding, and the decision to initiate therapy depends not only on the platelet count, but also on other endpoints including quality of life. The choice of first-line therapy depends primarily on how quickly a platelet count response is required, with intravenous immune globulin providing the more rapid response, followed by high-dose dexamethasone and prednisone. In this narrative review, we discuss key issues with first-line therapy in ITP including when to initiate therapy, treatment options and special considerations for children. Evidence-based guidelines are lacking for the emergency management of patients with ITP who present with significant bleeding; we provide our approach to this critical situation.
Keywords: platelet; autoimmune diseases; paediatric